Interactions of diarrhea, pneumonia, and malnutrition in childhood: recent evidence from developing countries - Schlaudecker, Elizabeth P. (Curr Opin Infect Dis, 2011)
PURPOSE OF REVIEW: This review highlights recent progress toward understanding complex interactions between diarrhea, pneumonia, and undernutrition among children in low-income and middle-income countries. RECENT FINDINGS: New studies parallel earlier reports that diarrhea and pneumonia impair children’s growth and that underlying malnutrition is a major risk factor for these conditions. Episodes of diarrhea may predispose to pneumonia in undernourished children. Additional studies support breastfeeding and micronutrient supplementation for the prevention and control of diarrhea and pneumonia. Malnutrition may partially account for the reduced efficacy of oral rotavirus vaccines in low-income countries. Immunization of pregnant women against influenza also appears to reduce intrauterine growth retardation. Immunization of infants against Streptococcus pneumoniae may improve their growth. New genetic studies indicate that polymorphisms in apolipoprotein E or the leptin receptor modulate children’s risk for diarrhea and Entamoeba histolytica infection, respectively, thereby linking two genes important for lipid metabolism to enteric infections. SUMMARY: Significant advances have been made in understanding the vicious cycle of malnutrition, diarrhea, and pneumonia in developing countries. Future challenges will be to translate this progress into effective and widely accessible public health measures.